Development and evaluation of extended-release vildagliptin tablets using quality by design - Pund, Atul K; Mundada, Atishkumar S (Creative Pharma Assent, 2024)
Background: Extended-release dosage forms are designed to enhance patient compliance and decrease dosing frequency. However, commercially available extended-release tablets are made with synthetic or semisynthetic controlled-release polymer, which causes a ghost pill effect. The ghost pill effect is minimized by using natural polymers which are biodegradable. Aim: This study aimed to create extended-release vildagliptin tablets using natural polymer by employing the quality by Design. Method: The study involved preparing granules of vildagliptin by direct compression using co-processed polymer and other excipients and compressing them into tablets. Results & Discussion: The different micromeritic characteristics of granules were satisfactory for compressing them into tablets. The FTIR, DSC, and XRD analysis indicates no interaction between the drug and the other excipients. The drug release shows that the marketed formulation releases 97% of the drug in 8 hrs., Whereas the developed formulation extends the drug release >= 95% throughout 12hrs. Drug release kinetic study results reveal that the optimized batch obeys first-order kinetics with the Higuchi model. In vivo studies showed steady plasma levels over an extended period, achieving the objective of the current study. The stability study carried out as per the ICH guideline exhibited robustness of the formulation, with the drug content found between 96 % to 99 % at 30°C & 75 %RH and 40°C & 75 %RH. Conclusion: The extended-release formulation of vildagliptin could be successfully formulated using a combination of natural and semisynthetic polymers. This combination could prove to be effective, safe, and well tolerated, enhancing patient adherence and lowering overdose risks, thereby reducing overall diabetic treatment costs.